TINJAUAN PEMBATALAN PENETAPAN PANITIA URUSAN PIUTANG NEGARA DAN RISALAH LELANG YANG DIKELUARKAN OLEH PEJABAT LELANG KELAS II MELALUI PENGADILAN TATA USAHA NEGARA (Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 531 K/TUN/2002) - , I GEDE WIRA NEGARA, Dwi Haryati, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was intended to identify and understand whether decision of confiscation order letter over confiscated goods (SPPBS) issued by PUPN is appropriate or not being sued in administrative court and to identify and understand auction report issued by class II auction official that can be cancelled through state administrative court. This research used normative juridical approach. Data used in this research is secondary data consisting of primary, secondary and tertiary law material. The data is collected through library study with documentary study technique. Primary data obtained from interview with informant was analyzed qualitatively with descriptive method. The result indicated that plaintiffâs suit in dispute number 531 K/TUN/2002 is less appropriate submitted to administrative court because decision of SPPBS come from unpaid credit agreement from state-owned bank that its content subject to civil law action that lead to auction in civil procedure, which is exemption of Article 2 paragraph a of Law on PTUN. SPPBS is not final because it requires follow up from other institution that is state auction office presented in auction report. SPPBS did not lead to legal effect for plaintiff because there is no transfer of right of collateral object to others. Therefore, the claim should be better sent to district court because its content is dispute on civil ownership that is under authority of district court. Auction report issued by class II auction official cannot be nullified through state administrative court, because the auction report did not meet perfectly elements of state administrative decision, particularly elements of state administrative decision object, in which auction report contain minute of auction containing civil law on civil sell-buy transaction, which is exemption from article 2 paragraph a of Law on PTUN so the claim should be better sent to general court.